Speed vs. Understanding: A Study of Student Readers - Wulandari, Sri; nursawalina, Nursawalina; Kristanti Yuntoro Putri (Universitas Islam Lamongan, 2024)
Reading is one of four skills that is needed to learn the English language. However, if it only reads without comprehending the passage, it only wastes time and will be useless. Therefore, a good reader should have a reading technique to make the reading process more effective. This research aimed to determine whether there is a correlation between students' reading speed and reading comprehension in the fourth-semester English Education Study Program of Universitas Islam Kadiri. This research used a correlation method. The sample of this research was used Non-Probability Sampling. It was a saturated sample. The sample of this research was 4th semester of class A English Students at Kadiri Islamic University. In collecting the data, the researcher used reading speed and multiple choices tests as instruments. A reading speed test was used to know students